2017
DOI: 10.1038/nature24014
|View full text |Cite
|
Sign up to set email alerts
|

Targeting neuronal activity-regulated neuroligin-3 dependency in high-grade glioma

Abstract: Summary High-grade gliomas (HGG) are a devastating group of cancers, representing the leading cause of brain tumor-related death in both children and adults. Therapies aimed at mechanisms intrinsic to the glioma cell have translated to only limited success; effective therapeutic strategies will need to also target elements of the tumor microenvironment that promote glioma progression. We recently demonstrated that neuronal activity robustly promotes the growth of a range of molecularly and clinically distinct … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
374
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 404 publications
(429 citation statements)
references
References 43 publications
19
374
0
Order By: Relevance
“…In the Figure I,J, we found that the level of NLGN3 was higher in the fundus region of GBM tissue compared to that in the surface region. Previous studies have shown that NLGN3 promotes the proliferation of gliomas by activating the PI3K‐mTOR pathway . Therefore, we further tested the level of p‐AKT (S473) in the GBM tissue and found that the level of p‐AKT (S473) was higher in the fundus region (Figure K,L).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In the Figure I,J, we found that the level of NLGN3 was higher in the fundus region of GBM tissue compared to that in the surface region. Previous studies have shown that NLGN3 promotes the proliferation of gliomas by activating the PI3K‐mTOR pathway . Therefore, we further tested the level of p‐AKT (S473) in the GBM tissue and found that the level of p‐AKT (S473) was higher in the fundus region (Figure K,L).…”
Section: Resultsmentioning
confidence: 81%
“…Furthermore, in Figure we noticed that GBM would grow to deeper brain regions over time after its recurrence. Previous studies have demonstrated that microenvironmental NLGN3 is essential for the growth of GBM . Therefore, we hypothesized that NLGN3 plays an important role in the recurrence of GBM.…”
Section: Resultsmentioning
confidence: 96%
“…The lack of FMRP in Fmr1 KO mice leads to enhanced synaptic targeting of NLGN1 and NLGN3. Synaptic stimulation provokes very rapid proteolytic cleavage of NLGN1 and NLGN3 at both WT and Fmr1 KO synapses and reported to serve as the mitogen promoting glioma growth [70,71]. NLGN1 and NLGN3 cleavage was also suggested by the proteomics study [69] and there is a report regarding NLGN2 cleavage in Drosophila [72].…”
Section: Discussionmentioning
confidence: 97%
“…However, we reckon that more detailed analysis is required to understand the molecular mechanism of activity-dependent NLGNs shedding at the synapse and its consequences for synaptic functions. To date, two specific secretory proteases were proposed to cleave NLGN1: matrix metalloproteinase 9 (MMP-9) [52] and disintegrin and metalloproteinase domain-containing protein 10 (ADAM-10) [53,[69][70][71]. Recently, the cleaved NLGN3 was detected in the medium from optogenetically stimulated acute cortical slices WT Fmr1 KO Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reveals that neurons could promote glioma growth through activity‐dependent secretion of neurotrophins, especially neuroligin‐3 (Venkatesh et al ., ). In addition, blocking neuroligin‐3 secretion by ADAM metallopeptidase domain 10 inhibitor shows a strong inhibition on the in vivo growth of gliomas (Venkatesh et al ., ). These studies highlight a crucial role of neuronal regulation on the aggression of gliomas and suggest that neuron‐derived neurotrophins are potential therapeutic targets for the treatment of gliomas (Johung and Monje, ).…”
Section: Introductionmentioning
confidence: 99%